Clinical Comparison of the Volumetric Changes in Single Pontic Site Development through Connective Tissue Grafting Using Modified Pouch Technique versus Pouch Technique in the Maxillary Esthetic Zone: A Randomized Controlled Clinical Trial - Ahmed H. Ammar; Enji Ahmed; Ahmed ElBarbary; Dalia Ghalwash; Azza Ezz Elarab (Hindawi Limited, 2022)
Aim. The aim is to compare the volumetric changes between pouch technique versus the modified pouch technique in pontic site development using connective tissue graft in patients that have Seibert class I ridge defects in the maxillary esthetic zone. Methodology. This randomized, controlled, double-blinded, parallel-grouped clinical trial included sixteen patients with a single pontic site in the maxillary esthetic area presenting Seibert Class I ridge defects. Patients were randomly assigned into two equal groups: test group (n: 8) received soft tissue augmentation with connective tissue graft using the modified pouch technique and control group (n: 8) received soft tissue augmentation with connective tissue graft using pouch technique. The volumetric evaluation was carried out by taking impressions at baseline, 3 and 6 months after the surgery. Keratinized tissue thickness was also measured at baseline, 3 and 6 months after the surgery. Visual analogue scale (VAS) was recorded by the patients at day 3, day 7, and day 14 after the surgery. Results. The test group had more increase in soft tissue volume than the control group at baseline, 3 months, and 6 months. The keratinized tissue width at baseline in the test group had a higher value than that of the control group. At 3 months, both groups had the same mean value, while at 6 months, the test group had a higher value than the control group. Regarding postoperative pain, the visual analogue scale shown at day 3 in the test group had a higher value than that of the control group, while at day 7, the control group had a higher value than the test group. At day 14, both groups had the same mean value. Conclusions. Soft tissue augmentation using both the traditional pouch technique and the modified pouch technique led to successful soft tissue volume augmentation in pontic site development in Seibert Class I ridge defects with no statistically significant difference between the two techniques.